Identifying Strategies to Cultivate Students’ Attitude Towards Circular Economy - Ab Hamid, Norzaharah; Rasul, Mohamad Sattar; Mohd Kamaruzaman, Fathiyah (Journal of Technical Education and Training, 2024)
Circular economy (CE) in Technical and Vocational Education and Training (TVET) refers to an economic approach that promotes efficient use of resources, material recovery, and waste reduction through vocational education. Despite various activities and programs conducted by TVET instructors to promote the circular economy, reports indicate that students’ attitudes towards the environment remain at a moderate level. This paper aims to identify strategies that can be implemented to foster students’ interest in practicing the circular economy within the context of TVET. This study uses the Nominal Group Technique (NGT) as an alternative approach to suggest initiatives that can foster students’ attitudes towards the circular economy. The process involved silent idea generation, round robin, discussion, two rounds of initial voting, and a final stage survey to determine the priority list. Five content experts participated in the NGT meeting. Initially, 50 strategies were identified. Through the NGT process, 20 important strategies were selected to cultivate students’ attitudes towards the circular economy. These strategies include waste management workshops, environmental programs and activities at institutions, conducive public sector ecosystem (EKSA) in institutions, homes and neighborhoods, information boards, simulation outside the classroom, daily routines, campaigns, neighborhood activities, sale of used oil, sale of recycled goods, innovation, waste segregation, cultivating student awareness, application in teaching, motivation, moral support, cleanliness and cheerfulness competitions, environment week, incorporating circular economy in the syllabus, and cross-curricular elements. The identified strategies are expected to assist stakeholders in overseeing the implementation of environmental awareness programs in schools, colleges, and TVET institutions, with the goal of improving student attitudes and transforming TVET education towards greater circular economy awareness.